Fluorescence-Guided Surgery and Biopsy in Gliomas with an Exoscope System. (21st May 2014) - Piquer, José; Llácer, Jose L.; Rovira, Vicente; Riesgo, Pedro; Rodriguez, Ruben; Cremades, Antonio
Abstract : Background . The introduction of fluorescence-guided resection allows a better identification of tumor tissue and its more radical resection. We describe our experience with a modified exoscope to detect 5 ALA-induced fluorescence in neuronavigation-guided brain surgery or biopsy of malignant brain tumors. Methods . Thirty-eight patients with a suspected preoperative diagnosis of high-grade astrocytoma were included. We used a neuronavigation device and a high-definition exoscope system with a built-in filter to detect 5-ALA fluorescence in all cases. Thirty patients underwent craniotomy with tumor resection and 8 underwent frameless stereotactic brain biopsy. Results . Histopathological diagnosis confirmed the presence of high-grade gliomas in 34 patients. Total resection was achieved in 23 cases and subtotal in 7. No relevant complications related to the administration of 5-ALA were detected. Conclusions . The use of the exoscope in 5-ALA fluorescence-guided tumor surgery has twofold implications: during brain tumor surgery it can be considered a valuable tool to achieve a more radical resection of the lesion, and when applied to a biopsy of a suspected brain high-grade glioma, it decreases the possibility of a negative biopsy.